All-Optical Tunability of Metalenses Permeated with Liquid Crystals - Palermo, Giovanna; Lininger, Andrew; Guglielmelli, Alexa; Ricciardi, Loredana; Nicoletta, Giuseppe; De Luca, Antonio; Park, Joon-Suh; Lim, Soon Wei Daniel; Meretska, Maryna L.; Capasso, Federico; Strangi, Giuseppe (American Chemical Society, 2022)
Metasurfaces have been extensively engineered to produce a wide range of optical phenomena, allowing exceptional control over the propagation of light. However, they are generally designed as single-purpose devices without a modifiable postfabrica-tion optical response, which can be a limitation to real-world applications. In this work, we report a nanostructured planar-fused silica metalens permeated with a nematic liquid crystal (NLC) and gold nanoparticle solution. The physical properties of embedded NLCs can be manipulated with the application of external stimuli, enabling reconfigurable optical metasurfaces. We report the all-optical, dynamic control of the metalens optical response resulting from thermoplasmonic-induced changes of the NLC solution associated with the nematic-isotropic phase transition. A continuous and reversible tuning of the metalens focal length is experimentally demonstrated, with a variation of 80 mu m (0.16% of the 5 cm nominal focal length) along the optical axis. This is achieved without direct mechanical or electrical manipulation of the device. The reconfigurable properties are compared with corroborating numerical simulations of the focal length shift and exhibit close correspondence.